(3GdQjGV GdfVQI aj efGbH GdYTQIs - (3CMeO Hf YHO Gddg Hf eMeO GdWHQj, CHh GdYHGS, eMH GdOjf,J (B694 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf Gddg SHMGfg hJYGdi bO GNJGQ dQShdg Udi Gddg Ydjg hSde hGUWai ef CUMGHg LedI GdYTQI aQVjge s
(3BNQgG (B:s
(3hbGdJ YGFTI QVi Gddg YfgG (B: (3QCjJ QShd Gddg Udi Gddg Ydjg hSde jbHd YKeGf Hf YaGf eXYhf hgh ejJ bGd MSHc dh bdJ cGf jMH Gddg hQShdg s
(3GfXQ HQbe (B" 1088" (3JGQjNs
(3fSNI KGfjIs
(3hHYV UaMGJgG HNW eZGjQs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs